Flies without centrioles. - Basto, R; Lau, J; Vinogradova, T; Gardiol, A; Woods, C; Khodjakov, A; Raff, J (2006)
Centrioles and centrosomes have an important role in animal cell organization, but it is uncertain to what extent they are essential for animal development. The Drosophila protein DSas-4 is related to the human microcephaly protein CenpJ and the C. elegans centriolar protein Sas-4. We show that DSas-4 is essential for centriole replication in flies. DSas-4 mutants start to lose centrioles during embryonic development, and, by third-instar larval stages, no centrioles or centrosomes are detectable. Mitotic spindle assembly is slow in mutant cells, and approximately 30% of the asymmetric divisions of larval neuroblasts are abnormal. Nevertheless, mutant flies develop with near normal timing into morphologically normal adults. These flies, however, have no cilia or flagella and die shortly after birth because their sensory neurons lack cilia. Thus, centrioles are essential for the formation of centrosomes, cilia, and flagella, but, remarkably, they are not essential for most aspects of Drosophila development.